Medicinal plants used by the indigenous Ati tribe in Tobias Fornier, Antique, Philippines - Cecilia Cordero; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2021)
Abstract. Cordero CS, Alejandro GJD. 2021. Medicinal plants used by the indigenous Ati tribe in Tobias Fornier, Antique, Philippines. Biodiversitas 22: 521-538. This study documented the medicinal plants used by the indigenous Ati tribe in Sitio Pantad, Brgy. Igcalawagan, Tobias Fornier, Antique. Semi-structured interviews were conducted with the tribal chieftain, council of elders, herb doctors, and other members of the tribe who have indigenous knowledge of using medicinal plants in traditional medicine. The Use Value, Informant Consensus Factor, and Fidelity Level were used to determine the plants’ importance. A total of 108 plant species distributed in 97 genera and 44 families were used by the Ati to treat 67 diseases in 12 categories. The family Fabaceae was best represented with 15 species, followed by Lamiaceae with 12 species, and Asteraceae, Euphorbiaceae, and Poaceae with 5 species each. The most frequently used part was the leaf and the most common method of preparation and administration was decoction that was taken orally. One of the most culturally important medicinal plants was Euphorbia hirta L. with the highest use value (0.59) for treating visual problems, dengue, typhoid fever, and headache. The result of this study serves as an ethnobotanical base for drug research and formulation, as well as creating the needed awareness for preserving ethnomedicine as a safe and effective alternative means in the health care delivery system.